Quelques aspects de la consommation du cricétome, Cricetomys (Rongeur), par des populations zaïroises - Malekani, M. (Tropicultura, 1989)
Some aspects of the consumption of the giant rat (Cricetomys Rodent), by populations in Zaire. An investigation made by us with 455 Zairean adults shows that the "cricetoma", also known as "giant rat", is found in all the eleven provinces of Zaire. This study permitted us to know 84 other names of this animal in 78 different local languages. Despite taboos and prohibitions which subsist in some places, the cricetoma meat is in high demand and well appreciated in general. According to the questionnaires, 64 % of people say that the taste of this meat is excellent. About the possibility to domesticate this animal, 50 % of people questionned agree this idea but 41 % do not accept it. The establishment of appropriate methods and techniques for an easy rearing in captivity can favourably permit its exploitation as a source of animal proteins.